A qualitative analysis of patients' reasons for choosing neobladder or ileal conduit after cystectomy for bladder cancer. (September 2016) - Osborne, Lisa A; Dixon, Catherine; Edwards, Darren J; Begum, Rahima; Younis, Ayman; Lucas, Malcolm; Reed, Phil
Objective: Choice of reconstruction following bladder removal is often between neobladder or ileal conduit diversion. Identifying patient concerns about this little understood choice should provide better understanding of factors important in making surgical decisions. The current study used a qualitative technique to identify patient concerns and values influencing patient choice of bladder reconstruction following radical cystectomy. Subjects and Methods: Thirty-two patients (neobladder: 11 male, 6 female; ileal conduit: 9 male, 6 female) participated in semi-structured interviews conducted at a Hospital Clinical Research Unit, and their responses were analysed by content analysis. Results: Many procedure and lifestyle factors were secondary to survival considerations. Most patients adapted to reconstruction. Patients chose neobladder because of perceptions of normality and less-restricted activities (including sex life), or chose ileal conduit because of perceived simplicity of this operation, or the fear of urinary incontinence, and extra 'work' for the patient involved in having a neobladder. Male and female reasons were consistent with one another, except that body image was a greater issue for females in choosing neobladder. Conclusion: Pre-existing concerns influenced the choice that patients made between undergoing illeal conduit or neobladder reconstruction after removal of their bladder. These findings are a step towards developing a tool to aid joint decision making when planning exenterative and reconstructive surgery for bladder cancer.